ANALISIS METODE RGEC UNTUK MENILAI TINGKAT KESEHATAN BANK PADA BPR KONVENSIONAL DI PROVINSI KEPULAUAN RIAU - Jurnal Akuntansi Barelang (JURNAL AKUNTANSI BARELANG, 2017)
The banking industry is financial institution that developed quite well in Indonesia. Basically the function of a bank is a financial institution that connects between the parties require funds to parties who have surplus funds , or can be said to be a collector of funds from surplus units and channeling funds to deficit units ( financial intermediary ) . According to the Financial Stability Review , the financial institution with the highest number is BPR . BPR growth must be balanced with a more healthy condition BPR anyway , in order to provide maximum service to the community and maintain the existence of the BPR . This study aims to determine how the soundness of the Bank in the period 2011 – 2015. This type of research is descriptive research with quantitative approach. The variables used were risk profile as measured by the ratio of NPL, LDR and BOPO, good corporate governance is measured through self- assessment results, profitability as measured by ROA and ROE, and Capital as measured by the ratio of CAR. The results showed that during the period 2011 to 2015 the Bank always obtain a rating of 1 or very healthy. NPL ratio calculation and LDR describe the bank has to manage risks properly. GCG assessment indicates corporate governance has done well. The calculation of ROA and NIM shows the bank's ability to achieve high profits. CAR calculation is always above the minimum limit Bank Indonesia is considered able to manage its capital. However, in the study the author also explains that the method of RGEC is not fully suitable to be applied in the BPR due to the method of GCG demanding opponess can not be met, because the data of the method of CGC is not publishhed in Bank Indonesia. As well as fully into the secret of the company.